The effect of absorbed hydrogen on the dissolution of steel. Issue 12 (December 2016) - Thomas, Sebastian; Ott, Noemie; Schaller, Rebecca F.; Yuwono, Jodie A.; Volovitch, Polina; Sundararajan, Guruprasad; Medhekar, Nikhil V.; Ogle, Kevin; Scully, John R.; Birbilis, Nick
Abstract: Atomic hydrogen (H) was introduced into steel (AISI 1018 mild steel) by controlled cathodic pre-charging. The resultant steel sample, comprising about 1 ppmw diffusible H, and a reference uncharged sample, were studied using atomic emission spectroelectrochemistry (AESEC). AESEC involved potentiodynamic polarisation in a flowing non-passivating electrolyte (0.6 M NaCl, pH 1.95) with real time reconciliation of metal dissolution using on-line inductively coupled plasma-atomic emission spectroscopy (ICP-OES). The presence of absorbed H was shown to significantly increase anodic Fe dissolution, as evidenced by the enhanced detection of Fe 2+ ions by ICP-OES. We discuss this important finding in the context of previously proposed mechanisms for H-effects on the corrosion of steels.